Fiscal Policy Surveillance in the enlarged European Union: Procedural Checks or Simple Arithmetic? - Groenendijk, Nico (Emerging European Financial Markets, 2006)
In its recommendation on the 2004 update of the Broad Economic Policy Guidelines (BEPGs), the European Commission (2004) issued country-specific recommendations for fiscal policy in the Central and Eastern European (CEE) countries that have recently joined the European Union (EU) (henceforth the EU-10 countries). All countries except Estonia and Slovenia were urged to reduce their general government deficits, or to pursue low budget deficits in a credible and sustainable way within the multi-annual framework of EU budgetary surveillance. Some countries have received additional recommendations (the Czech Republic to reform its health care and pension systems, Estonia and Lithuania to avoid pro-cyclical policies, and Poland to reform its pension system). Most new Member States will consequently have to reduce their fiscal deficits and/or will have to avoid pro-cyclical fiscal policies to comply with the BEPGs, but also because of the required convergence within the Economic and Monetary Union (EMU). Bearing in mind that the government balance for the new Member States was –5.7 per cent of gross domestic product (GDP) in 2003, the required reduction of fiscal deficits will not be easy. This has been acknowledged by the Commission, which has argued that the need to reach and maintain sound budgetary positions will require an appropriate time path between the necessary consolidation and the appropriate fiscal stance supporting the transition. Particular attention will also need to be given to country-specific circumstances, in particular to initial budgetary positions, to ongoing structural shifts in the new Member State economies, and to the possible risks resulting from current account imbalances and strong credit growth.